Diet order significantly affects energy balance for diets varying in macronutrients but not ultraprocessing in crossover studies without a washout period - Sciarrillo, Christina M; Guo, Juen; Hengist, Aaron; Darcey, Valerie L; Hall, Kevin D (The American journal of clinical nutrition, 2024)
Crossover studies can induce order effects, especially when they lack a washout period. We performed secondary analyses comparing groups of subjects randomly assigned to different diet orders in 2 inpatient crossover studies originally designed to compare within-subject differences in ad libitum energy intake. One study compared minimally processed low-carbohydrate (LC) compared with low-fat (LF) diets, and the other matched macronutrients and compared minimally processed food (MPF) with ultraprocessed food (UPF) diets. Diet order group comparisons of changes in body weight and body composition, and differences in energy expenditure and food intake were assessed over 4 wk in 20 adults randomly assigned to either the LC followed immediately by the LF diet (LC → LF) or the opposite order (LF → LC), and 20 adults randomly assigned to either the MPF followed by the UPF (MPF → UPF) diets or the opposite order (UPF → MPF). Subjects randomly assigned to LC → LF lost 2.9 ± 1.1 kg more body weight (P <0.001) and 1.5 ± 0.6 kg more body fat (P = 0.03) than the LF → LC group, likely because the LC → LF group consumed 921 ± 304 kcal/d less than the LF → LC group (P = 0.003). These energy intake differences were driven by the last 2 wk (−1610 ± 312 kcal/d; P < 0.0001), perhaps because of carryover effects of gut adaptations during the first 2 wk arising from large differences in the mass of food (1296 ± 215 g/d; P <0.00001) and fiber consumed (58 ± 6 g/d; P <0.00001). There were no significant diet order effects on energy intake, body weight, or body composition changes between UPF → MPF and MPF → UPF groups. Diet order significantly affected energy intake, body weight, and body fat in a 4-wk crossover inpatient diet study varying in macronutrients, but not in a similarly structured study varying in ultraprocessed foods. This trial was registered at clinicaltrials.gov as NCT03407053 and NCT03878108.